Into the Deep: New Data on the Lipid and Fatty Acid Profile of Redfish Sebastes mentella Inhabiting Different Depths in the Irminger Sea - Viktor P. Voronin; Nina N. Nemova; Tatjana R. Ruokolainen; Dmitrii V. Artemenkov; Aleksei Y. Rolskii; Alexei M. Orlov; Svetlana A. Murzina (Biomolecules, 2021)
New data on lipid and fatty acid profiles are presented, and the dynamics of the studied components in muscles in the males and females of the beaked redfish, Sebastes mentella, in the depth gradient of the Irminger Sea (North Atlantic) is discussed. The contents of the total lipids (TLs), total phospholipids (PLs), monoacylglycerols (MAGs), diacylglycerols (DAGs), triacylglycerols (TAGs), cholesterol (Chol), Chol esters, non-esterified fatty acids (NEFAs), and wax esters were determined by HPTLC; the phosphatidylserine (PS), phosphatidylethanolamine (PE), phosphatidylinositol (PI), phosphatidylcholine (PC), and lysophosphatidylcholine (LPC) were determined by HPLC; and fatty acids of total lipids were determined using GC. The Chol esters prevailed in muscles over the storage TAGs, and the wax ester content was high, which is a characteristic trait of vertically migrating species. Specific dynamics in certain PL in redfish were found to be depended on depth, suggesting that PLs are involved in the re-arrangement of the membrane physicochemical state and the maintenance of motor activity under high hydrostatic pressure. The high contents of DHA and EPA were observed in beaked redfish muscles is the species’ characteristic trait. The MUFAs in muscles include dietary markers of zooplankton (copepods)—20:1(n-9) and 22:1(n-11), whose content was found to be lower in fish sampled from greater depths.